Pengukuran Kinerja Keuangan Menggunakan Alat Ukur Economic Value Added (EVA) Dan Market Value Added (MVA) - Umi Rahma Dhany; Hery Koeshardjono; Indah Agustin (Ecobuss, 2023)
The purpose of this research is to find out the results of financial performance based on the method of Economic Value Added (EVA) and Market Value Added (MVA) in companies in the pharmaceutical sub-sector in 2016-2020. The type of research used is descriptive quantitative, with the variable Economic Value Added (EVA) and Market Value Added (MVA). The population in this research are pharmaceutical sub-sector companies listed on the IDX. The sample selection used the purposive sampling technique and seven companies were selected that met the criteria set by the researcher. The results show that there four companies whose Economic Value Added (EVA) value is positive or > 0 then it can be said to be able to create economic added value for the company so that financial performance can be said to be good and all companies have a positive Market Value Added (MVA) value or > 0 indicating it can increase the value of capital so that financial performance can be said to be good.